Creating variable developmental situations in primary school lessons - Zaitsev S.V., P (Moscow State University of Psychology and Education, 2017)
The paper discusses the intensity of learning motivation in university students of various forms, stages and courses of education and its relationship with personal reflection. Large amounts of empirical data obtained in this research allow us to assert that the adequacy of learning motivation is higher in graduate students than in undergraduate students, the latter demonstrating the highest rates in their first year of study and the lowest in the third. Motivation rates in part-time undergraduate students tend to decrease during the first three years at university; however, the rates increase in the fourth year. We also compared learning motivation in respondents with different levels of reflective thinking. Asit was revealed, adequate motivation and motives for acquiring the profession were higher in students with high levels of reflection as compared to those displaying average and low levels. Moreover, the highest rates of reflection were found in students who planned to pursue their profession and knew exactly in which field, whereas the lowest rates were common for students who were not certain as to whether their work would correspond with their major discipline.